Eating pattern and educational history in women of childbearing age - Syamsul Alam; Dian Ihwana Ansyar; Muhammad Fais Satrianegara (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
Chronic energy deficiencies often occur and attack women of childbearing age. this illustrates insufficient energy and protein intake and it can result in health and unbalanced nutritional patterns. The purpose of this study was to determine the relationship between diet and educational history with the incidence of chronic energy deficiency in women of childbearing age in Gunturu Village, Herlang District, Bulukumba, Province of South Sulawesi. This research was conducted in 2019 with a total sample of 359 people, the design of this study was cross sectional study, data collection through interviews using questionnaires and direct observation, data of Chronic energy deficiencies obtained through LiLA measurements, consumption patterns obtained through interviews using the FFQ Form, and it was analyzed statistically with the chi square test. The result shown that the eating patterns of most respondents were in the good category and did not experience KEK. While the majority of respondents with less eating patterns did not experience KEK. Respondents who had never attended school, respondents had completed elementary / junior high / high school education, and respondents who graduated from tertiary institutions mostly did not experience KEK. The absence of a statistically significant relationship between diet and education was likely to be influenced by the proportion of WUS who experience a lower KEK that was 45 people than WUS who did not experience KEK as many as 314 people. Researchers hope that the community can maintain healthy living behaviors by managing a good diet, like watching the type of food consumed